Inovasi Media Pembelajaran Sistem Starter Berbasis Induksi untuk Optimalisasi Hasil Belajar Siswa SMK Bidang Otomotif - Widiyatmoko Widiyatmoko; Destian Dwi Sulistyohadi; Dhimas Suranto; Zain Alfaridzi; Dhimas Ichsani Setyo (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to (1) Determine the characteristics and elements in the learning media of the automotive induction model starter system to suit the characteristics of TKRO students of SMK YPT Purworejo. (2) Evaluate the feasibility aspects of the learning media of the automotive induction model starter system in terms of content, design, interactivity, and functionality. (3) Determine the improvement in learning outcomes of the starter system competency by developing learning media in the form of an automotive induction model starter system trainer for class XI Automotive Light Vehicle Engineering students of SMK YPT Purworejo. The type of research used is Research and Development. The subjects in this study were class XI TKR students of SMK YPT Purworejo. Data collection was carried out using questionnaire and test methods. After the questionnaire was validated, it was then tested on a limited basis to 20 students. The calculation of the questionnaire and test instruments used the point biserial validity formula or Y_pbis with a significance level of 5%. The results of the study showed that the learning media of the automotive induction model starter system has characteristics in the form of interactive visual displays, systematic materials, and the use of attractive colored acrylic media in accordance with the characteristics of TKRO students. Student learning outcomes in the experimental class increased by 13%, with an average score of 78.17. This indicates that students are more active and motivated by the use of learning media.